BOOK REVIEWS (Heythrop journal, 1985)
Book Reviewed in this article: Traditional Sayings in the Old Testament. By Carole R. Fontaine. Pp. viii, 279, Sheffield, The Almond Press, 1982, £17.95 (hardback), £8.95 (paperback). The First Day of the New Creation: The Resurrection and the Christian Faith. By Vesilin Keisch. Pp.206, Crestwood, New York, St Vladimirs Seminary Press, 1982, £6.25. The First Day of the New Creation: The Resurrection and the Christian Faith. By Vesilin Keisch. Pp.206, Crestwood, New York, St Vladimir's Seminary Press, 1982, £6.25. The Resurrection of Jesus: A Jewish Perspective. By Pinchas Lapide. Pp.160, London, SPCK, 1983, 4.95. Easter Enigma. By John Wenham. Pp.162, Exeter, Paternoster Press, 1984, £2.95. The Anastasis: the Resurrection of Jesus as an Historical Event. By J. Duncan M. Derrett. Pp.xiv, 166, Shipston-on-Stour, P. Drinkwater, 1982, £5.00. The Open Heaven: A Study of Apocalyptic in Judaism and Early Christianity. By Christopher Rowland. Pp. xii, 562, London, SPCK, 1982, £22.50. Christianity Rediscovered: An Epistle from the Masai. By Vincent J. Donovan. Pp. viii, 200, London, SCM Press, 1982, £5.50. Basics of a Roman Catholic Theology. By William A. Van Roo, S.J. Pp.387, Rome, Gregorian University Press, 1982, $21.00. Charisms and Charismatic Renewal: a Biblical and Theological Study. By Francis A. Sullivan. Pp.184, Dublin, Gill & Macmillan, 1982, £5.95. Holiness and Politics. By Peter Hinchliff. Pp.214, London, Darton, Longman and Todd, 1982, £8.95. Rational Theology and the Creativity of God. By Keith Ward. Pp.240, Oxford, Blackwell, 1982, £14.00. The Point of Christology. By S.M. Ogden. Pp.xii, 193 (The 1980 Sarum Lectures), London, SCM Press, 1982, £5.95. Fullness of Humanity: Christ's Humanness and Ours. By T.E. Pollard. Pp.126 (The 1980 Croall Lectures), Sheffield, The Almond Press, 1982, £9.95 (hardback), £5.95 (paperback). Milton's Good God: A Study in Literary Theodicy. By Dennis Richard Danielson. Pp.xi, 292, Cambridge University Press, 1982, £20.00. Biblical Tradition in Blake's Early Prophecies: The Great Code of Art. By Leslie Tannenbaum. Pp.xiii, 373, Princeton University Press, 1982, £17.60. The Inner Journey of the Poet and Other Papers. By Kathleen Raine, edited by Brian Keeble. Pp.xii, 208, London, George Allen and Unwin, 1982, £9.95. i Vol. 34: Horayot and Niddah. Translated by Jacob Neusner. Pp.xiii, 243 (Chicago Studies in the History of Judaism), Chicago, The University of Chicago Press, 1982, £17.50. Holy Land Pilgrimage in the Later Roman Empire A.D. 312–460. By Ed. Hunt. Pp. £+ 269, Oxford University Press, 1982, £16.50. Constantine versus Christ: The Triumph of Ideology. By Alistair Kee. Pp.186, London, SCM Press, 1982, £5.95. Society and the Holy in Late Antiquity. By Peter Brown. Pp.347, London, Faber and Faber, 1982, £10.50. Elishe: History of Vardan and the Armenian War. Translation and commentary by Robert W. Thomson. Pp.x, 353, 1 map, Cambridge (Mass.), Harvard University Press, 1982, £21.00. Ireland in Early Mediaeval Europe: Studies in Memory of Kathleen Hughes. Edited by Dorothy Whitelock, Rosamond McKitterick and David Dumville. Pp.x, 406, Cambridge University Press, 1982, £39.00. Letters from Ireland 1228–1229 by Stephen of Lexington. Translated with an introduction by B.W. O'Dwyer. Pp.vii, 292, Kalamazoo, Cistercian Publications, 1982, $24.95. The Occupation of Celtic Sites in Ireland by the Canons Regular of St Augustine and the Cistercians. By Geraldine Carville. Pp.ix, 158, Kalamazoo, Cistercian Publications, 1982, $13.95. Chartres: The Masons who built a Legend. By John James. Pp.200, London, Routledge and Kegan Paul, 1982, £17.50. Temples, Churches and Mosques: A Guide to the Appreciation of Religious Architecture. By J.G. Davies. Pp.x, 262, Oxford, Basil Blackwell, 1982, £12.50. The Murdered Magicians: The Templars and their Myth. By Peter Partner. Pp.xxi, 209. Oxford University Press, 1982, £12.95. The Italian Crusades: The Papal-Angevin Alliance and the Crusades Against Christian Lay Powers, 1254–1343. By Norman Housley. Pp.xi, 293, Oxford, Clarendon Press: Oxford University Press, 1982, £17.50. The Westminster Chronicle, 1381–1394. Edited and Translated by L.C. Hector and Barbara F. Harvey. Pp.lxxvii, 563. Oxford, the Clarendon Press, 1982, £42.00. Frömmigkeitstheologie am Anfang des 16. Jahrhunderts. By Berndt Hamm. Pp.xv, 378 (Beiträge zur historischen Theologie), Tübingen, J.C.B. Mohr (Paul Siebeck), 1982, 168 DM. Erasmi Opera omnia, IX, 2: Desiderii Erasmi Roterodami Apologia respondens ad ea quae Iambus Lopis Stunica taxavrat in prima duntaxat Novi Testamenti aeditione. Edited by Henk Jan de Jonge. Pp.292, Amsterdam, North-Holland Publishing Company, 1983, 280 guilders. The Christian Polity of John Calvin. By Harro Höpfl. Pp.x, 303, Cambridge University Press, 1982, £27.50. Concerning the Eternal Predestination of God. By John Calvin, translated with an Introduction by J.K.S. Reid. Pp.191, Cambridge, James Clarke & Co., 1982, £5.95. Spanish Protestants and Reformers in the Sixteenth Century: A Bibliography. By A. Gordon Kinder. Pp.108, London, Grant & Cutler, 1983, £6.80. Moderate Puritans and the Elizabethan Church. By Peter Lake. Pp.viii, 357, Cambridge University Press, 1982, £27.50. Resistance and Compromise: The Political Thought of Elizabethan Catholics. By Peter Holmes. Pp.viii, 279, Cambridge University Press, 1982, £22.50. Dutch Puritanism: A History of English and Scottish Churches of the Netherlands in the Sixteenth and Seventeenth Centuries. By Keith L. Sprunger. Pp.xiii, 485, Leiden, E.J. Brill, 1982, 172 guilders. John Toland and the Deist Controversy. By Robert E. Sullivan. Pp.viii, 355, Cambridge (Mass.), Harvard University Press, 1982, £19.95. Radical Sects of Revolutionary New England. By Stephen A. Marini. Pp. 213, Cambridge (Mass.), Harvard University Press, 1982, £11.55. Religion and Society in North America: An Annotated Bibliography. Edited by Robert deV: Brunkow. Pp.xi, 515, Santa Barbara, ABC-Clio; Oxford, EBC-Clio, 1983, £57.75. Charles Lowder and the Ritualist Movement. By Lida Ellsworth. Pp.vi, 234, London, Darton, Longman & Todd, 1982, £17.95. How the Pope became Infallible: Pius IX and the Politics of Persuasion. By August Bernhard Hasler. Pp.xi, 383, New York, Doubleday, 1981, $14.95; London, Sheldon Pres, 1982, £15.00. Hauptsache der Papst ist katholisch. Edited by Bruno Nies. Pp.104, Salzburg, Otto Müller, 1982, öS 140. Religious Change in Contemporary Poland: Secularization and Politics. By Maciej Pomian-Srednicki. Pp.227, London, Routledge & Kegan Paul, 1982, £12.50. World Christian Encyclopedia: A Comparative Survey of Churches and Religions in the Modern World. Edited by David B. Barrett. Pp.1010, Nairobi, Oxford University Press, 1982, £55.00. Probability and Evidence. By Paul Horwich. Pp.vii, 146 (Cambridge Studies in Philosophy), Cambridge University Press, 1982, £15.00. Philosophical Foundations of Probability Theory. By Roy Weatherford. Pp.xi, 282 (International Library of Philosophy), London, Routledge and Kegan Paul, 1982, £15.00. The Origins of Greek Thought. By Jean-Pierre Vernant. Pp.144, London, Methuen, 1982, £9.95. Portraying Analogy. By J.F. Ross. Pp.xi, 244 (Cambridge Studies in Philosophy), Cambridge University Press, 1981, £20.00. The Marriage of East and West. By Bede Griffiths. Pp.224, London, Collins, 1982, £5.95. The Religious Experience: A Socio-Psychological Perspective. By C.D. Batson & W.L. Ventis Pp.ix, 356, New York, Oxford University Press, 1982, £18.50 (hardback),£9.95 (paperback).